Recent Advances in the Therapeutic Strategies of Glioblastoma Multiforme. (21st May 2022) - Aldoghachi, Asraa Faris; Aldoghachi, Ahmed Faris; Breyne, Koen; Ling, King-Hwa; Cheah, Pike-See
Highlights: Glioblastoma is the most common primary malignant brain tumor and is a challenging disease to treat. The current standard of care includes surgical resection, followed by a combination of radiation and chemotherapy. Glioblastoma has a high recurrence rate, urging scientists to continue to search for more effective treatment options. Advanced therapies includes thermo-, nano-, immuno-, and phototherapy; and tumor treating fields. Abstract: Glioblastoma multiforme (GBM) is one of the most common, most formidable, and deadliest malignant types of primary astrocytoma with a poor prognosis. At present, the standard of care includes surgical tumor resection, followed by radiation therapy concomitant with chemotherapy and temozolomide. New developments and significant advances in the treatment of GBM have been achieved in recent decades. However, despite the advances, recurrence is often inevitable, and the survival of patients remains low. Various factors contribute to the difficulty in identifying an effective therapeutic option, among which are tumor complexity, the presence of the blood–brain barrier (BBB), and the presence of GBM cancer stem cells, prompting the need for improving existing treatment approaches and investigating new treatment alternatives for ameliorating the treatment strategies of GBM. In this review, we outline some of the most recent literature on the various available treatment options such as surgery, radiotherapy, cytotoxic chemotherapy, gene therapy, immunotherapy, phototherapy, nanotherapy, and tumor treating fields in the treatment of GBM, and we list some of the potential future directions of GBM. The reviewed studies confirm that GBM is a sophisticated disease with several challenges for scientists to address. Hence, more studies and a multimodal therapeutic approach are crucial to yield an effective cure and prolong the survival of GBM patients.